Voltammetric determination of auramine o with ZIF-67/Fe2O3/g-C3N4 modified electrode - Dang Thi Ngoc Hoa; Tran Thanh Tam Toan; Tran Xuan Mau; Nguyen Thi Vuong Hoan (TV); Tran Thi Nhat Tram; Tran Duc Manh; Vo Thang Nguyen; Vu Thi Duyen; Pham Le Minh Thong; Dinh Quang Khieu (My University, 2020)
Voltammetric determination of auramine o with ZIF-67/Fe2O3/g-C3N4 modified electrode
Keywords: Auramine o